Niemann-Pick Disease: Seven Questions about it - Nato D. Vashakmadze; Nataliya V. Zhurkova (Вопросы современной педиатрии, 2023)
Acid sphingomyelinase deficiency is a rare hereditary disease caused by enzyme deficiency due to mutations in the SMPD1 gene. Decreased enzyme activity leads to accumulation of sphingomyelin in lysosomes. This disease is characterized by wide diversity of clinical manifestations: from infantile neurovisceral form (Niemann-Pick disease type A) with severe rapidly progressive neurodegeneration to chronic visceral form (Niemann-Pick disease type B) with almost no central nervous system involvement. There is also intermediate phenotype: chronic neurovisceral form (Niemann-Pick disease type A/B) that includes manifestations two other forms, both visceral and neurological. The disease course is most commonly progressive and multi-system due to sphingomyelin accumulation in cells of the monocyte-macrophage system, as well as in other cells such as hepatocytes.